Feminist Perspectives on Post-riot Judicial Inquiry Commissions in India. (August 2017) - Rajeshwari, B.
This article argues that though communal riots bring different experiences for men and women, yet this reality does not seem to be recognized by post-riot justice mechanisms. Justice post-riots is viewed as a 'blanket' term for all the victims irrespective of their gender. In so doing, women's everyday experiences seem to get pushed under the carpet. Drawing from feminist critique of the legalistic approach to justice, this article problematizes the understanding that there is only one singular, official version of truth in post-riot situations. The article critically examines post-riot judicial commissions that were constituted to inquire into the Mumbai (1992–1993) and Gujarat (2002) riots from a feminist perspective. I argue that the judicial inquiry commissions in their current format are underequipped to deal with gender concerns that emerge after communal riots. And that there is a need for feminist security studies to venture into critically analyzing judicial inquiry commissions.